The effects of intraoperative use of blue dyes in pediatric pilonidal sinus disease-a retrospective exploratory cohort study - Marie N. Engels; Britta Lüken-Darius; Christina Oetzmann von Sochaczewski; Andreas C. Heydweiller (SpringerOpen, 2024)
Abstract Background Intraoperative use of methylene blue has been shown to reduce postoperative complications and recurrence rates in adults. It has however not been assessed if these beneficial effects would also apply to pediatric pilonidal sinus disease with its high recurrence rates. We, therefore, aimed to assess its effects on complications and recurrences in our retrospective exploratory cohort study. Methods Of 55 consecutive children treated in our centre between January 2009 and December 2020, 48 were retrospectively included. We used logistic regression with a priori chosen predictors of intraoperative use of blue dyes, previous surgery for pilonidal sinus disease, and the presence of comorbidities on the composite outcome of complications and recurrence. Cramér's V was used to explore associations between the use of blue dyes and the extent of resection. Results The median age in our cohort was 15.3 years. Five patients were below 2 years of age, and 24 (50%) of them were males. Chronic diseases were present in 13 (27%) patients, eight had previously been operated on for pilonidal sinus disease, and blue dyes were used in 34 patients (71%). Their intraoperative use was linked to the composite outcome with an odds ratio of 5.41 (95% confidence interval (CI) 1.52-25.34, P = 0.017) as were comorbidities with an odds ratio of 1.86 (95% CI 1.18-3.25, P = 0.014), but not re-do surgery (odds ratio 2.94 (95% CI 0.37 23.42, P = 0.3)). The use of blue dyes was associated with larger resections (Cramér's V 0.556 (95% CI 0.329-0.74)). Conclusion The intraoperative use of blue dyes was negatively associated with complications and recurrences in pediatric pilonidal sinus disease. However, if blue dyes were used, the extent of resection was also larger. Larger resections had been shown before to be associated with complications and recurrences, too. This potential interaction requires further elucidation in future studies.